(3GdacQ GdMOjK aj gjcd Jehjd GdTQcGJ (B/s - (3gfOj, efjQ GHQGgjes ((3GdGScfOQjI(B: s (3efTCI GdeYGQa(B, s, 2005)
(3JcdaI GdhcGdI aj GWGQ fXQjI GdefTCI, GdChQGb GdeGdjI GdeSJMOKI, JCKjQ GdGbJQGV Ydi GdbjeI GdShbjI ddefTCI, GSJNOGe GdbQhV ceUOQ ddJehjd, GdCQHGM GdeMJLRI ceUOQ HOjd, GdGSJMhGP hGdGfOeGL GdCSGdjH hSHd GdJehjd, GdNUNUI, GdJehjd GdOhdjs
(3GdedGMb U(B.620s
Keywords: (3GdEOGQI GdeGdjIs; (3GdChQGb GdeGdjIs; (3GdTQcGJ(B- (3Jehjds; (3GdbQhVs